HOTEL AS HERITAGE SITE BUILDING; FROM INDONESIA PERSPECTIVE (Hotel sebagai Bangunan Cagar Budaya berdasarkan perspektif Indonesia) - Agung Gita Subakti (Jurnal Hospitality dan Pariwisata, 2017)
Purpose- The purpose of this research is to classify the characteristic of hotel industry that are classified as heritage building site in Indonesia, to describe its strategic management, and to define the advantages and obstacles encountered Methodology- This is qualitative research with descriptive analysis method. Primary data was collected from key informant interview and questionnaire survey with hotel management representative. Research was conducted at selected hotels inIndonesia, which are listed officially at Indonesia heritage inventory website Expected Findings- The result will provide depth description refer to major principles of hotel concept as heritage building; its characteristic, competitive advantages, strategic management, its operational and all related challenges that might be occured Research limitation- First is limitation in the number of selected hotel. Second, analysis is only from hotel management point of view. Thus further research should be conducted for hotels in all Indonesia area considering perspective from employee, government and expert perspective Value- This research contributes to the understanding for hotel industry acknowledgement in the depth concept of heritage hotel. As the result, it will be a benchmarking for other hotel to conduct their operations strategic especially for those that will be listed as heritage building Keywords: Heritage, hotel, heritage hotel, overview, heritage building